FAKTOR-FAKTOR YANG MEMPENGARUHI SUKU BUNGA PINJAMAN MODAL KERJA, TINJAUAN PADA BANK PEMERINTAH DAERAH DI INDONESIA - Yulianti, Veronika; Dedy (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aim to determine the effect of Working Capital Loan Interest Rate, Inflation, Population Growth Rate and sight of Local Government Bank in Indonesia. In addition, there is also a balance or relationship between free variables and non-free variables in this research model, in case for long term or short term within using multiple linier regression method. The increase of population growth rate make working capital also increase, especially at Local Government Bank in Indonesia. The data that use in this research is secondary data’s for annual between Januari 2019 until December 2023 that published by Central Statistics Agency either Population Growth Rate, and Indonesian Bank either Inflation Rate and Working Capital Loan Interest Rate. The types of The loan distribution in question is the Working Capital Loan Interest Rate. The results of this study show that inflation has an effect on working capital loan interest rates because high inflation rates can have an impact on banking interest rates. Similarly, the rate of population growth has a significant effect on the interest rate on working capital loans because the rate of population growth will increase the demand for goods and services.